An Analysis of Teachers’ Practices in Teaching Reading Literacy in Elementary Schools - Fatihah, Salma Nur; Winarni, Retno; Daryanto, Joko (Universitas Sebelas Maret, 2026)
Teachers play a central role in creating effective reading literacy learning for elementary school students, encompassing technical skills, comprehension, reasoning, and critical use of information. This study aims to analyze the role of teachers, describe strategies for reading literacy learning, and identify challenges faced by teachers. This study used a descriptive qualitative approach with a case study method. Data were collected through learning observations, in-depth interviews with classroom teachers, and analysis of Lesson Plan (RPP) documents at SDN Celep 02 Sukoharjo. The results show that teachers act as facilitators, motivators, and reader models by implementing strategies such as reading aloud, integrated discussions, and guided reading assignments tailored to students' abilities. Teachers also strive to create a learning environment that supports reading habits, but still face obstacles such as limited time, a lack of variety in teaching materials, and difficulties in handling students with low initial reading abilities. The conclusion of this study confirms that optimizing reading literacy learning requires ongoing support through teacher professional development, diverse learning resources, and supportive school policies.